Dormitory Supervisor Communication Strategy in Developing Student Morals - Japeri, Japeri; Santika, Nora; Pangestu, Ario Bimo; Nalus, Syafrul (Suluah Pasaman, 2024)
Communication strategy is used in the world of da'wah so that what is conveyed can run smoothly and the message can be communicated. This research is motivated by the problem, there are still many students who live in dormitories who violate the rules, such as not praying on time, being lazy in worship, not understanding the importance of morals, not being able to respect guests, and lacking civility in their daily lives. This research aims to determine the communication strategies used by female dormitory supervisors in developing student morals at the junior high school level in Indonesia. This research uses a qualitative method with a case study type. Data sources were taken from ten informants through direct interviews using a set of interview protocols. The informants consisted of dormitory supervisors and students who lived in the dormitory. All interview data was analyzed thematically using the Milles & Hubberman Interactive Analysis Model technique. Research findings found four strategies implemented by dormitory coaches in developing students' morals. These strategies are providing advice, setting an example, carrying out good habits or training, and giving punishment if it does not comply with Islamic rules. Apart from that, the results of this research can be used as a reference for anyone who wants to manage a dormitory at school.